(untitled) (Journal of Management and Social Sciences, 2022)
This study examined the effects of public expenditure on income growth in Nigeria using Vector Auto-regressive Analysis (VAR). The results show that real income responds positively to public expenditures on administration, community services, defence and economic services. The results also confirm the feed-back effects of income and government expenditures on administration, community services, defence and economic services. It was concluded that government should direct her expenditure policies to favoured expenditures that positively impact the growth of real national income and per capita income. Hence, government should increase and judiciously manage her expenditure on administration, economic services, defence and community services. Corrupt practices in government should also be drastically curbed for effective usage of fiscal allocation.